Development of iSpring Suite 11 to train students’ numeracy literacy through problem posing - Depi Setialesmana; Sinta Verawati Dewi; Linda Herawati; Dedi Nurjamil (University of Muhammadiyah Malang, 2025)
Learning of direct and indirect proportions continues to face significant challenges, as many students struggle to grasp the fundamental concepts and their applications. A lack of relevant interactive learning media is one factor that affects students' conceptual understanding and numerical literacy skills. This study aims to develop iSpring Suite 11 learning media, focusing on the validity and practicality of the media while identifying students' numerical literacy categories and stages of problem posing. Validity and practicality are prioritized to ensure that the media meet academic and pedagogical standards and are easy to implement. Initial feedback is essential for improvement before evaluating the media's effectiveness. The research employs a Research and Development (R&D) methodology using the PPE model. Subject matter experts and media specialists conducted media validation, supplementing it with small- and large-scale trials to assess practicality. The results indicate that iSpring Suite 11 learning media demonstrate high validity and practicality, as evaluated by material and media experts. Among the 70 participating seventh-grade students, 21 exhibited high numeracy literacy, 31 were categorized as medium, and 18 were identified as low. An analysis of problem-posing stages revealed that 71.42% of students were in the pre-solution posing stage, 15.71% were in the within-solution posing stage, and only 12.85% achieved the post-solution posing stage. These findings suggest that, although the media have been validated as both valid and practical, further research is necessary to measure their effectiveness in enhancing students' numeracy literacy through pre- and post-test evaluations.